1964
DOI: 10.1002/ange.19640762103
|View full text |Cite
|
Sign up to set email alerts
|

Photochemische Substitutionen an Metallcarbonylen und deren Derivaten

Abstract: Durch die vor einigen Jahren gefundene photochemische Reaktion von n‐ und π‐Donatoren mit Metallcarbonylen oder deren Derivaten kann man ein breites Spektrum neuer Metallcarbonyl‐Derivate herstellen, welche thermisch nicht oder nur mit schlechten Ausbeuten zu erhalten sind. — Präparative Verfahren werden beschrieben. An ausgewählten Beispielen wurde der Reaktionsmechanismus dieser photochemisch induzierten Substitutionsreaktionen aufgeklärt und versucht, einen Einblick in die Polarität der Metall‐Liganden‐Bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

1967
1967
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(36 citation statements)
references
References 55 publications
1
32
0
3
Order By: Relevance
“…W(CO) 5 [P(OCH 3 ) 3 ] [9], cis-W(CO) 4 (piperidine) 2 [10], W(CO) 4 (g 2:2 -norbornadiene) [11] and W(CO) 4 (g 2:2 -1,5-cyclooctadiene) [12] were prepared according to the literature procedures. (0), W(CO) 5 (pyz), (1), and l-pyrazine-bis(pentacarbonyltungsten(0)), (CO) 5 W(pyz)W(CO) 5 , (2) Following the procedure [2] pyrazine (pyz, 0.454 g, 5.68 mmol) was added to a solution of W(CO) 5 (thf) photogenerated [13] from W(CO) 6 (1.0 g, 2.84 mmol) in 250 mL tetrahydrofuran (thf) at 10°C. After mixing for 2 h, the volatiles were removed under vacuum.…”
Section: General Proceduresmentioning
confidence: 99%
“…W(CO) 5 [P(OCH 3 ) 3 ] [9], cis-W(CO) 4 (piperidine) 2 [10], W(CO) 4 (g 2:2 -norbornadiene) [11] and W(CO) 4 (g 2:2 -1,5-cyclooctadiene) [12] were prepared according to the literature procedures. (0), W(CO) 5 (pyz), (1), and l-pyrazine-bis(pentacarbonyltungsten(0)), (CO) 5 W(pyz)W(CO) 5 , (2) Following the procedure [2] pyrazine (pyz, 0.454 g, 5.68 mmol) was added to a solution of W(CO) 5 (thf) photogenerated [13] from W(CO) 6 (1.0 g, 2.84 mmol) in 250 mL tetrahydrofuran (thf) at 10°C. After mixing for 2 h, the volatiles were removed under vacuum.…”
Section: General Proceduresmentioning
confidence: 99%
“…Tetrahydrofuran (THF) mit UV-Licht bestrahlt. Die gebildete Lösung von Mo(CO)5 • THF setzt man dann mit 3,32 g 2 (10 mmol) um [15]. Aus Diethylether/Chloroform, ockerfarbene Kristalle.…”
Section: -Chlor-4-(di-t-butylphosphino)-5-methoxy-2 (5h )-Furanonunclassified
“…Previously, molybdenum aminecarbonyls have been prepared using molybdenum hexacarbonyl as the starting material following a variety of methods among them the following (i) UVirradiation of an amine/hexacarbonyl mixture [1,2], refluxing a carbonyl/amine mixture in a suitable solvent [3] and an indirect method whereby some of the CO groups are substituted with hydrocarbon ligands such as cyclohexatriene, norbornadiene or mesitylene and the products thus obtained are reacted with an amine [4,5]. In a previous study, it was shown that the halocarbonyls, [Mo(CO) 4 X 2 ] 2 (X = Cl, Br), react with primary amines either neat or in an alcohol such as ethanol or methanol as a solvent at ordinary conditions of temperature and pressure to form aminecarbonyls of the type, Mo(CO) 3 L 3 (L = propylamine, butylamine, cyclohexylamine) which could not be obtained by refluxing an amine/hexacarbonyl mixture [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was shown that the halocarbonyls, [Mo(CO) 4 X 2 ] 2 (X = Cl, Br), react with primary amines either neat or in an alcohol such as ethanol or methanol as a solvent at ordinary conditions of temperature and pressure to form aminecarbonyls of the type, Mo(CO) 3 L 3 (L = propylamine, butylamine, cyclohexylamine) which could not be obtained by refluxing an amine/hexacarbonyl mixture [6]. Piperidine, however, reacts with these halocarbonyl to give Mo(CO) 4 (piperidine) 2 even when the halocarbonyl is refluxed with the neat base [7,8]. During these studies, piperididine was, however, the only base that gave an identifiable organic oxidation product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation